TARI TAK OYAI DI KAMPUANG AIE DUKU KANAGARIAN PAINAN TIMUR â€œPEMARGINALAN DAN KEBERTAHANAN DALAM KONTEKS PELESTARIANâ€ - Arita, Arita (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2015)
Tak Oyai dance is a cultural heritage of the community of Pesisir Selatan Regency, particularly Painan Timur. The research focused on Tak Oyai dance in the Aie Duku Village, where the dance is herited from their ancestors. This research used qualitative method; where data is collected by observation, interviews, and documentation using equipments such as video and audio recorder, also camera. Research findings prove that Tak Oyai dance is recognized as a cultural heritage in the social and cultural life of the community, however it is not recognized as the current tradition and culture of the Aie Duku community, therefore it is rarely presented in entertaining and ceremonial event. In the other hand there is still an attempt preserve the dance although not yet successful.